Concomitant immune‐related events in Wilson disease: implications for monitoring chelator therapy. Issue 1 (12th June 2015) - Seessle, Jessica; Gotthardt, Daniel Nils; Schäfer, Mark; Gohdes, Annina; Pfeiffenberger, Jan; Ferenci, Peter; Stremmel, Wolfgang; Weiss, Karl Heinz
Abstract: Background and Aims: Current guidelines favor the use of chelating agents (d‐penicillamine, trientine) in first line therapy of symptomatic Wilson disease patients. Development of chelator induced immunological adverse events are a concern especially under d‐penicillamine therapy. This study assessed the prevalence of co‐existing or therapy‐related immune‐mediated diseases in Wilson disease patients, and evaluated the role of antinuclear antibodies in therapy monitoring. Methods: We retrospectively analyzed 235 Wilson disease patients. Medical regimens were classified and analyzed in relation to adverse events and antinuclear antibody courses. Results: Coexisting immune‐mediated diseases were evident in 19/235 (8.1 %) patients, of which 13/235 (5.5 %) had pre‐existing autoimmune diseases. Six patients (2.6 %) developed an autoimmune disease under therapy, all of them under long‐term d‐penicillamine treatment. Data relating to antinuclear antibody courses during treatment and adverse events were available for patients treated with d‐penicillamine ( n  = 91), trientine ( n  = 58), and zinc salts ( n  = 58). No significant increase in antinuclear antibody titers in patients treated with d‐penicillamine (16/91; 17.6 %), trientine (12/58; 20.7 %), and zinc (7/58; 12.1 %) were found. Conclusion: Under long‐term d‐penicillamine therapy a minority of patients developed immune‐mediated disease. Elevations in antinuclear antibodies were found frequently, but no correlations were evident between increases in antinuclear antibodies and the development of immune‐mediated diseases or medical regimes. Thus, the value of antinuclear antibodies for monitoring adverse events under chelator therapy seems to be limited.